Colombia : Technical Assistance Report-Detailed Assessment of Observance of Key Attributes of Effective Resolution Regimes for Financial Institutions-Pilot of the Draft Assessment Methodology. (IMF Staff Country Reports; Country Report ;, 2016)
This paper provides a detailed assessment of key attributes of effective resolution regimes for financial institutions in Columbia. The authorities of Columbia have strong powers to manage weak and failing financial institutions and a track record of using them. Colombia's resolution regime, however, has shortcomings with respect to standards set in the key attributes. Important resolution powers are not available to the authorities, the regime does not emphasize minimizing the exposure of taxpayers to loss, and taking resolution actions does not hinge on an assessment of non-viability. However, Columbia has a large and diversified financial system compared with peer countries, with significant cross-border institutions and large mixed function conglomerates.